Themes and perspectives in Indian sociology - Dhanagare, D. N. (Jaipur, India Rawat Publications, 2013)
The essays in this volume critically review the development of sociology in India which has established itself in the world of scholarship. Taking the position of an (3z(Boutsider within(3y(B, the author has surveyed the themes and perspectives that dominated sociological concerns reflected in the literature produced by Indian sociologists from 1950s to late 1980s. s